(untitled) (Journal for Studies in Humanities and Social Sciences, 2015)
The Zimbabwean challenges witnessed between 1998 and 2008 brought about various survival strategies. Whereas some sought to create coping mechanisms within Zimbabwe, others went into exile. These two groups, nonetheless, needed to confront the massive challenges during the decade of the Zimbabwean considerable suffering (1998-2008). These included hyperinflation, unemployment, food shortages, violence and the high death rates. Creative writings played a significant part as authors depicted Zimbabweans who sought to survive in varied ways. Of particular importance to this article, is how one particular Zimbabwean female creative writer Tagwira employed her creative imagination to challenge the status quo. In The Uncertainty of Hope Tagwira (2006) represents her female characters in a more empowering way. She shows how they seek to overcome major challenges to ensure that their families survive the challenges.